Exploring new channels of communication - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
The CTA Annual Report 2004, available again on CD-ROM this year, outlines some of the most recent developments at the Centre.